Estimation of the burden of high-volume disease among metastatic hormone-sensitive prostate cancer patients presenting to urologists in Pakistan - Aziz Abdullah, Liaqat Ali, Ahmed Fawad, Naveed Iqbal, Navira Chandio, Irfan Hashemy (Journal of Rawalpindi Medical College, 2022)
Introduction:There is a scarcity of data in Pakistan, describing the extent of metastases in men with hormone-sensitive prostate cancer (HSPC).We aimed first to determine the proportion of high-volume/extensive disease among metastatic HSPC patients, presenting to urologists. Secondly, to evaluate the profile of these patients and theiradherence to the treatment plan. Materials and Methods:This prospective observational study recruited consenting men with metastatic HSPC between October 2016 and September 2018. The high-volume disease was defined by the presence of visceral metastases or four or more bone lesions with at least one beyond the vertebral bodies and pelvis. Adherence to the treatment plan was observed during a period of three and six months. Descriptive statistics were used for the analysis of categorical and continuous variables. Results:The study included 100 patients fromfive cities inPakistan. Their mean and standard deviation (SD) of age was 69.2 ± 9.9 years. Performance status 2 was reported in 45% (n=45/100) patients, and Gleason score 8-10 in 69% (n=69/100). High-volume disease was prevalent in 68% (n=68/100) of patients, with bone metastases positive in 91% (n=91/100). Visceral metastases were identified in 26% (n=26/100) of patients with 10% reported in the lungs. At three and six months, physicians reported that 90% (n=85/94) and 91% (n=81/89) of patients adhered to the planned treatment, with hormonal manipulation in 86% (n=81/94) and 88% (n=78/89) respectively. Conclusion:Our first nationwide study in Pakistan demonstrated a high metastatic burden among HSPC patients presenting to a urologist. A multidisciplinary team approach, with the early involvement of oncologists, is imperative for the most appropriate management. Keywords: Prostatic Neoplasms, Carcinoma, Metastasis, Urologists, Pakistan.